Transhemispheric exchange of Lyme disease spirochetes by seabirds. - Olsen, B (1995)
Lyme disease is a zoonosis transmitted by ticks and caused by the spirochete Borrelia burgdorferi sensu lato. Epidemiological and ecological investigations to date have focused on the terrestrial forms of Lyme disease. Here we show a significant role for seabirds in a global transmission cycle by demonstrating the presence of Lyme disease Borrelia spirochetes in Ixodes uriae ticks from several seabird colonies in both the Southern and Northern Hemispheres. Borrelia DNA was isolated from I. uriae ticks and from cultured spirochetes. Sequence analysis of a conserved region of the flagellin (fla) gene revealed that the DNA obtained was from B. garinii regardless of the geographical origin of the sample. Identical fla gene fragments in ticks obtained from different hemispheres indicate a transhemispheric exchange of Lyme disease spirochetes. A marine ecological niche and a marine epidemiological route for Lyme disease borreliae are proposed.